KERAGAAN INDUSTRI PANGAN OLAHAN BERBASIS TEPUNG UBI KAYU DI KABUPATEN MALANG DAN TRENGGALEK - Hanafie, SRDm Rita (Jurnal Sosial Ekonomi Pertanian, 2014)
The study aims to determine the performance of processed food industry based on cassava flour viewed from its characteristics which cover business orientation, growth process, business development, production process, technology, and efforts to fulfilling the resources; as well as the development strategy. The study was conducted in district of Malang and Trenggalek, were selected intentionally (purposive sampling).The industry based on cassava flavour is determined by Data Based Triangulation. The research sample is determined by Snowball Sampling. The results showed that the processed food industry based on cassava flour which is growing in Malang and Trenggalek is mocaf cracker industry and mocaf sticks. The industry characteristics are: product-oriented, process grows on the basis of excess commodities that are not optimally used, have the capital, has the experience, and have confidence in the ability to take advantage of these commodities; business development is indicated by the growth of the asset; production process is easy and quick; simple technology; and the easy supply of resources. On the basis of the identification of 11 driver factors and 13 inhibiting factors, the development strategy are to optimize the utilization of local producers of cassava flour that involving the government, businesses, local communities, organizations and local institutions to develop the processed food industry based on cassava flour. Keywords: performance, processed food industry, cassava flour